Dual drug-induced aseptic meningoencephalitis: More than a suggestion. (June 2021) - Coletti Moja, Mario; Riva, Giovanna; Catalfamo, Edoardo
We present the case of a patient with a first single episode of a dual drug-induced aseptic mening (DIAM) due to amoxicillin and ibuprofen and a short review of updated literature. A 76-year-old man was admitted to our hospital with slowness and confusion following a dental and gingival inflammation treated with oral amoxicillin 500 mg bid and ibuprofen 600 mg tid for 1 week. His mental state and higher functions abruptly worsened after therapy increase leading to hospitalization. Both the drugs were stopped and the patient improved rapidly within 2–3 days and was released asymptomatic after a week. On the basis of this temporal relationship with a comprehensive negative neuroimaging and laboratory testing for viral, bacterial, and mycobacterial micro-organisms, a DIAM by amoxicillin and ibuprofen was diagnosed. We support the hypothesis that this dual therapy was causative because of the progressive onset of central nervous system symptoms starting at a low amoxicillin dose with a high ibuprofen intake and that this sort of chemical meningoencephalitis was mostly due to the pharmacokinetic of amoxicillin after its dose increase. To our knowledge, this is the first documented publication of a severe first episode of DIAM with predominant higher function involvement caused by these two drugs commonly used together, amoxicillin and ibuprofen.